2015
DOI: 10.1021/cb501028c
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Conjugates Carrying Sequentially Assembled Trivalent N-Acetylgalactosamine Linked Through Nucleosides Elicit Robust Gene Silencing In Vivo in Hepatocytes

Abstract: Asialoglycoprotein receptor (ASGPR) mediated delivery of triantennary N-acetylgalactosamine (GalNAc) conjugated short interfering RNAs (siRNAs) to hepatocytes is a promising paradigm for RNAi therapeutics. Robust and durable gene silencing upon subcutaneous administration at therapeutically acceptable dose levels resulted in the advancement of GalNAc-conjugated oligonucleotide-based drugs into preclinical and clinical developments. To systematically evaluate the effect of display and positioning of the GalNAc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
151
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 21 publications
1
151
0
2
Order By: Relevance
“…The Alnylam group has further optimized the chemistry of the glycoconjugates, providing simpler alternatives for synthesis (259,260). Multivalent glycoconjugates have also been used to target novel uncharged siRNA entities (47) with the attainment of similar functional effects in cells and in vivo .…”
Section: Approaches To Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The Alnylam group has further optimized the chemistry of the glycoconjugates, providing simpler alternatives for synthesis (259,260). Multivalent glycoconjugates have also been used to target novel uncharged siRNA entities (47) with the attainment of similar functional effects in cells and in vivo .…”
Section: Approaches To Deliverymentioning
confidence: 99%
“…In this context, it is interesting to compare effects of the siRNA glycoconjugates described above with those of recent types of siRNA LNPs. While both approaches can effectively silence expression of hepatic genes, the LNP system can do so a doses of 0.1 mg/kg as compared to >5 mg/kg for the glycoconjugate (175,259). A final issue concerns stability.…”
Section: Approaches To Deliverymentioning
confidence: 99%
“…siRNA conjugates have emerged as an alternative to nanocarrier-mediated delivery (9)(10)(11)(12)(13)(14), offering the possibility of improving siRNA pharmacokinetics without requiring a more complex delivery vehicle. Alnylam Pharmaceuticals has demonstrated high gene silencing potency of a trivalent N-Acetylgalactosamine (GalNAc) siRNA conjugate, which binds with high specificity and affinity to the asialoglycoprotein receptor on hepatocytes (15,16).…”
mentioning
confidence: 99%
“…Additionally, recent studies with double stranded siRNA GalNAc conjugates have also demonstrated the need for appropriate positioning of trivalent GalNAc sugars for optimal activity. 32,33 In conclusion, single stranded chemically modified ASOs can be effectively delivered to hepatocytes using two and even a single GalNAc sugar. This can significantly reduce the structural complexity associated with manufacturing such conjugates for clinical applications.…”
mentioning
confidence: 94%